2015
DOI: 10.1177/2048872615574110
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, safety and feasibility of an evidence-based insulin infusion protocol targeting moderate glycaemic control in intensive cardiac care units

Abstract: The Desio Diabetes Diagram i.v. 140-180 protocol, fully managed by nurses, with insulin and glucose intravenous infusion proved effective, safe and feasible in maintaining blood glucose between 140 and 180 mg/dL in patients with diabetes or hyperglycaemia admitted to the intensive cardiac care unit for acute cardiac events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Furthermore, current standard IV insulin protocols also require hourly BG testing. 45,46 While continuous glucose monitoring, either SC or intravascular are not current options in the inpatient setting, if these tools ever become available the ability to control glycemia should become less burdensome. [47][48][49][50][51] Additional limitations of our study are the small cohort and the lack of a control arm.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, current standard IV insulin protocols also require hourly BG testing. 45,46 While continuous glucose monitoring, either SC or intravascular are not current options in the inpatient setting, if these tools ever become available the ability to control glycemia should become less burdensome. [47][48][49][50][51] Additional limitations of our study are the small cohort and the lack of a control arm.…”
Section: Discussionmentioning
confidence: 99%
“…A relatively tight glucose level (4.4–6.1 mmol/L) was initially recommended to reduce short-term adverse events in hospitalized diabetic patients after CABG [ 3 ]. However, an increasing number of studies have shown that tight glucose control may not be as beneficial as originally thought [ 4 , 5 ], particularly in patients undergoing On-Pump CABG. Blood glucose fluctuations were more common in patients with strict blood glucose control, resulting in worse outcomes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%